THE INFLUENCE OF THE BOARD DIVERSITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE INTHE LISTED COMPANY OF INDONESIA STOCK EXCHANGE (IDX) - Retno Fitri Febrianty; Nadia Anridho (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2025)
This study aimed to identify and examine the influence of board diversity on corporate social responsibility disclosure. Public companies (excluding companies in the financial sector) registered in the Indonesia Stock Exchange (BEI) in the year 2016-2018 were used in this study. There are 1250 samples obtained from purposive sampling that has met determined criteria. This study uses a quantitative approach with the ordinary least square (OLS) analysis method with SPSS ver.24 software. This study's result shows that board diversity has a significant negative effect on corporate social responsibility disclosure. This result indicates that the more diverse board of directors, the lower company’s corporate social responsibility disclosure.